Effects of pointing compared with naming and observing during encoding on item and source memory in young and older adults. Issue 9 (20th October 2016) - Ouwehand, Kim; van Gog, Tamara; Paas, Fred
ABSTRACT: Research showed that source memory functioning declines with ageing. Evidence suggests that encoding visual stimuli with manual pointing in addition to visual observation can have a positive effect on spatial memory compared with visual observation only. The present study investigated whether pointing at picture locations during encoding would lead to better spatial source memory than naming (Experiment 1) and visual observation only (Experiment 2) in young and older adults. Experiment 3 investigated whether response modality during the test phase would influence spatial source memory performance. Experiments 1 and 2 supported the hypothesis that pointing during encoding led to better source memory for picture locations than naming or observation only. Young adults outperformed older adults on the source memory but not the item memory task in both Experiments 1 and 2. In Experiments 1 and 2, participants manually responded in the test phase. Experiment 3 showed that if participants had to verbally respond in the test phase, the positive effect of pointing compared with naming during encoding disappeared. The results suggest that pointing at picture locations during encoding can enhance spatial source memory in both young and older adults, but only if the response modality is congruent in the test phase.